Determination and Contamination Assessment of Heavy Metals in Street Dust from Different Types of Land-Use in Kathmandu District, Nepal - Shakya, Sudarshana; Baral, Samikshya; Belbase, Priya; Siddique, Mohd Nur E Alam; Samoh, Abd Naser HJ; Das, Banani; Shrestha, Prem Kumar; Shakya, Pawan Raj (Journal of Institute of Science and Technology, 2019)
A total of forty seven street dust samples, collected from five different types of land use viz., industrial, urban, heavy traffic road, residential and undisturbed areas (control) of Kathmandu district (Nepal), were subjected to characterize the physico-chemical parameters such as pH, electrical conductance (EC), total alkalinity (T. Alk), total organic carbon (TOC) and particle size distribution. Four heavy metals of Cd, Cu, Pb and Zn were determined in dust samples using flame atomic absorption spectrophotometer (FAAS). It was found that all types of dust samples possessed alkaline nature along with variation in EC, T. Alk and TOC values. Results revealed that the dust of industrial areas contained high concentrations of Zn (143.3 mg/kg) and Cu (106.42 mg/kg), whereas the heavy traffic areas were mainly affected by Cd (0.90 mg/kg) and Pb (70.08 mg/kg). The average metal concentrations of Cd, Cu, Pb and Zn in dust of all the types of land use in Kathmandu were found to be 0.73, 68.86, 51.46 and 104.30 mg/kg and their average metal enrichment factors were 2.28, 5.50, 1.92 and 3.17, respectively. The results were also compared against heavy metals status in street dust from various cities/countries around the world. Pollution indices such as contamination factor (CF), degree of contamination (CD) and geo-accumulation index (Igeo) showed different classes of metal contamination in street dust of Kathmandu indicating traffic emission, automobiles, construction and demolition activities and other anthropogenic activities as the potential sources.